Histone Acetylation at the Promoter for the Transcription Factor PuWRKY31 Affects Sucrose Accumulation in Pear Fruit . Issue 4 (11th February 2020) - Li, Xinyue; Guo, Wei; Li, Juncai; Yue, Pengtao; Bu, Haidong; Jiang, Jing; Liu, Weiting; Xu, Yaxiu; Yuan, Hui; Li, Tong; Wang, Aide
Abstract : High acetylation in the promoter of a transcription factor gene is associated with sucrose accumulation in pear fruit by activating the expression of a sucrose transport gene. Abstract: Sugar content is an important trait of fleshy fruit, and elevating Suc levels is a major goal in horticultural crop breeding. Here, we examined the sugar content in two varieties of the Ussurian pear ( Pyrus ussuriensis ), 'Nanguo' (NG) and its bud sport (BNG), and we found that Suc content was higher in BNG fruit than in NG fruit. We compared the transcriptomes of the two varieties using RNA sequencing and identified a SWEET ( Sugars Will Eventually be Exported Transporter ) gene, PuSWEET15, expressed at higher levels in BNG fruit. Heterologous expression of PuSWEET15 in a SUSY7/ura yeast ( Saccharomyces cerevisiae ) strain showed that PuSWEET15 is an active Suc transporter. Overexpression of PuSWEET15 in NG pear fruit increased Suc content, while silencing of PuSWEET15 in BNG fruit decreased Suc content. The WRKY transcription factor PuWRKY31 was also expressed more highly in BNG fruit than in NG fruit, and we found that PuWRKY31 bound to the PuSWEET15 promoter and induced its transcription. The histone acetylation level of the PuWRKY31 promoter was higher in BNG fruit, suggesting a mechanism by which Suc levels can be elevated.